2007
DOI: 10.1002/ange.200703289
|View full text |Cite
|
Sign up to set email alerts
|

A Metallanaphthalyne Complex from Zinc Reduction of a Vinylcarbyne Complex

Abstract: Transition metal containing metallaaromatics are a fascinating class of compounds because they can show properties of both organometallic compounds and aromatic organic compounds.[1] The most common metallaaromatics are metallabenzenes, stable examples of which have been found for osmium, [2] iridium, [3] platinum, [4] and ruthenium. [5] Other interesting metallaaromatics and related compounds isolated in recent years include metallanaphthalene, [6] metallapyrylium, [7] metallathiabenzene, [8] metallapyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…26 Jia, Lin, and co-workers synthesized the first metallanaphthalyne in 2007 (Scheme 18, right). 43 We discovered the synthesis of osmanaphthalene and osmanaphthalyne unexpectedly in 2009, when we studied the thermal and air stability of osmium hydride alkenylcarbyne 36. 44 Heating 36 in ClCH 2 CH 2 Cl under a N 2 atmosphere afforded the (μ-Cl) 3 -bridged bisosmanaphthalene 50, while under an O 2 atmosphere osmanaphthalyne 51 was produced.…”
Section: Osmanaphthalene and Osmanaphthalynementioning
confidence: 99%
“…26 Jia, Lin, and co-workers synthesized the first metallanaphthalyne in 2007 (Scheme 18, right). 43 We discovered the synthesis of osmanaphthalene and osmanaphthalyne unexpectedly in 2009, when we studied the thermal and air stability of osmium hydride alkenylcarbyne 36. 44 Heating 36 in ClCH 2 CH 2 Cl under a N 2 atmosphere afforded the (μ-Cl) 3 -bridged bisosmanaphthalene 50, while under an O 2 atmosphere osmanaphthalyne 51 was produced.…”
Section: Osmanaphthalene and Osmanaphthalynementioning
confidence: 99%
“…1). Until now, well-defined cyclic metal carbynes were only known for third-row transition metal centers osmium and rhenium, namely, osmabenzynes (7)(8)(9), rhenabenzynes (10), osmapyridynes (11), osmapentalynes (12,13), and dirhenadehydro [12]annulenes (14), whereas these complexes with non-third-row transition metals have not yet been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Initial unsuccessful attempts : We have previously shown that reaction of zinc with the osmium vinyl carbyne complex [OsCl 3 {≡CCHC( o ‐ClC 6 H 4 ) 2 }(PPh 3 ) 2 ] produced a dichlorido–osmanaphthylyne complex and an unstable chloridohydrido–osmanaphthylyne complex 18d. The reaction was assumed to proceed through the 16 e − four‐coordinated square‐planar osmium carbyne complex [OsCl{≡CCHC( o ‐ClC 6 H 4 ) 2 }(PPh 3 ) 2 ], which undergoes oxidative addition reactions that involve CCl and CH bonds.…”
Section: Resultsmentioning
confidence: 99%